ON THE SPACES OF ?m-BOUNDED AND ?m-ABSOLUTELY p-SUMMABLE SEQUENCES - Ercan, Sinan; Bektas, Cigdem Asma (Univ Nis, 2017)
In this paper, we give the notion of lambda(m)-boundedness and p-absolute convergence of type lambda(m) and using these notions we define new sequence spaces. We examine some topological and geometric properties of these spaces. We also establish some inclusion relations concerning these spaces and characterize some matrix classes.
Keywords: BK-Spaces; triangle matrix; alpha-, beta-, gamma-duals; Schauder basis; Matrix transformations; geometric properties